Issue Voting as a Voting Determinant in The Electoral Politics of District Charsadda - Dr. Muhammad Ibrahim; Mr. Khurshid Iqbal; Miss. Saleema Khattak; Mr. Abdul Qayum Khan; Dr.Tahira Batool (Al-Qanṭara, 2023)
The electoral behaviour of the public of District Charsadda especially NA-8 in the province of Khyber Pakhtunkhwa is examined in this paper. The study predicted issue voting as an important determinant in the electoral politics of district Charsadda. For the prediction of the electoral behaviour in the universe, survey has been conducted using questionnaire as a tool of data collection. Analysis made via descriptive and inferential statistics including Chi-Square test and probability value. The Primary data disclosed that (89.82%) of the respondents supported the electoral preferences made on the basis of issue voting in district Charsadda in 2013 general elections. Keywords- Elections, Charsadda, Issue voting, Voting Behaviour